Universal Automation Framework: Revolutionizing Test Automation Architecture - Sujeeth Manchikanti Venkata Rama, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The Universal Automation Framework (UAF) represents a transformative approach to test automation that addresses the persistent challenges faced by organizations in maintaining effective testing strategies. This comprehensive article explores how UAF's tool-agnostic architecture revolutionizes test automation by introducing a standardized, maintainable, and efficient framework that adapts to evolving technology stacks. Through its innovative object repository management, virtual application modeling, and unified test case structure, UAF enables organizations to overcome traditional automation limitations while significantly improving test coverage, reducing maintenance overhead, and enhancing overall software quality. The framework's implementation demonstrates substantial benefits across multiple dimensions, including standardization, productivity, cost optimization, and quality improvements, making it particularly valuable for enterprises managing diverse technology stacks and complex testing environments.
Keywords: Automation Framework; Quality Improvement; Software Testing; Test Maintenance; Tool-Agnostic Architecture